Design and Construction of an Anemometer. - Mukhangu, Paul (Kabale University, 2024)
This research report examined the advancements in anemometer technology and their implications for meteorology and renewable energy. Anemometers play a crucial role in measuring wind speed and direction, essential for weather forecasting, environmental monitoring, and optimizing wind energy systems. The study aims to address current limitations in anemometry by designing and evaluating a more accurate and robust prototype Historical development reveals significant milestones in anemometer evolution, from early wind vane instruments to sophisticated sensor-based devices. Recent research emphasizes the need for enhanced accuracy, durability, and cost-effectiveness in anemometer design to overcome. The research adopts a true experimental design, manipulating wind speed as an independent variable to assess its impact on turbine performance metrics. Data collection methods include surveys, measurements, and observations, supported by advanced statistical analysis to interpret findings rigorously. Calibration techniques and quality assurance protocols ensure the reliability and validity of experimental outcomes. The proposed study aims to contribute valuable insights to the field of anemometry, particularly in advancing technology for more precise wind measurements. Findings are expected to enhance weather prediction models, optimize wind energy systems, and facilitate a better understanding of wind patterns and their environmental impact. The implications extend to diverse applications in aviation, environmental monitoring, and air quality assessment, underscoring the broader significance of improved anemometer technology.